Implementation of TQM in public universities of Saudi Arabia : challenges and resolutions - Alseddiqi, Abdul Rahman Ghassan (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
Recent developments in Total Quality Management (TQM) have underscored the need for more studies on this topic. Many Saudi universities have implemented TQM programs, but they are still struggling to reap the desired benefits. So, this work aims to analyze the current situation of public universities in Saudi Arabia, in view of the implementation of TQM, and to explore the challenges and resolutions of TQM implementation in Saudi public universities in order to achieve higher academic excellence. Questionnaires survey and interviews were adopted in this research for data collection. Subsequently, Quality Function Deployment (QFD) was applied in order to identify the challenges of implementing TQM in public universities of Saudi Arabia and to assess and select the critical resolutions to overcome those challenges. This research contributes to the existing body of knowledge in the field of TQM, as well as providing insight to public universities of Saudi Arabia in order to achieve higher academic excellence. Thus, Saudi universities will be able to produce effective and skillful graduates who can contribute in improving the productivity and the economy of Saudi Arabia. Keywords: Higher education in Saudi Arabia, Total Quality Management, Quality Function Deployment.